Registration of 'FL24D', a Red Clover Selected for Tolerance to 2, 4‐D Herbicide. Issue 3 (8th May 2015) - Quesenberry, Kenneth; Blount, Ann; Munoz, Patricio; Ferrell, Jason; Dubeux, Jose
Abstract : 'FL24D' (Reg. No. CV‐33 PI 673130) red clover ( Trifolium pratense L.) is a synthetic cultivar selected for tolerance to the herbicide 2, 4‐dichlorophenoxyacetic acid (2, 4‐D), and it is the most nondormant red clover cultivar available in today's market. Red clover can experience significant broad‐leaf weed competition, especially during the establishment phase of a sward. Most such weeds can be controlled in grass‐based forage systems with inexpensive herbicides such as 2, 4‐D since most grass species are naturally tolerant. However, 2, 4‐D is not a herbicide option in red clover that is sensitive to this herbicide. Beginning with a broad‐based red clover germplasm, six cycles of selection for tolerance to 2, 4‐D were conducted, leading to the development of FL24D. In a greenhouse experiment comparing response of FL24D to 'Southern Belle' (a 2, 4‐D‐sensitive cultivar) at a 1.06 kg ha −1 rate, FL24D rated 7.0 whereas Southern Belle rated 1.2 (where 9 = no damage and 1 = dead plant). A flowering experiment revealed that FL24D was 25 d earlier to 50% flowering than Southern Belle and 20 d earlier to 95% flowering than Southern Belle. Results from several cultivar evaluation experiments show that under sward conditions, application of 2, 4‐D herbicide at the recommended rate did not decrease yields of FL24D but did affect yields of cultivars that do not have tolerance to 2, 4‐D.